Nosocomial infections in the intensive care units - Jovanović Biljana; Mazić Nataša; Mioljević Vesna; Obrenović Jelena; Jovanović Snežana (Vojnosanitetski Pregled)
Background/Aim. The risk for nosocomial infections (NIs) is 5-10 times higher in patients hospitalized in the Intensive Care Units (ICUs) than in patients staying in other wards. The higher incidence rates of NIs in the ICUs may be explained by the fact that the patients in the ICUs have more severe underlying disease, and are exposed to the invasive diagnostic and therapeutical procedures. The unreasonable use of antibiotics leads to the selection of multiresistant agents, which have been increasingly recorded as the NIs causative agents. The aim of this study was to investigate the characteristics of NIs in the ICUs in the period January-June 2005. Methods. The study of incidence was performed in accordance with the methodology of the Centers for Diseases and Prevention. Any infections in the patients hospitalized in the ICUs in the period from January to June 2005 were registered. The results both from medical documentation and from the direct contacts with the medical personnel were analyzed. The samples were tested using standard methods in the microbiological laboratory. Results. The incidence rates of NIs patients ranged from 1.5 to 40.8, and the incidence rates of infections were 1.5 to 65.6 per 1 000 patient’s days. Out of the total number of NIs, urinary infections accounted for 44.6%, blood infections for 37.6%, and surgical site infections for 16.9%. Conclusion. The most frequent cause of nosocomial urinary infections was Klebsiella, of nosocomial sepsis - coagulase − negative staphylococci, and of surgical site infections - Staphylococcus aureus.